La voce di Ariel: Sylvia Plath e la transustanziazione della parola poetica (ENTHYMEMA, 2023)
This article aims to discuss the marked turn that characterizes the final stage of Sylvia Plath’s poetry. By reading selected passages from Ariel, in the restored edition that corresponds to Plath’s meticulously conceived sequence, I will outline the coordinates of a project that echoes ancient cosmologies, as Plath attempts to give birth to a new and more intimate world, finally free of painful separations. Without any doubt, a sense of creation pervades Ariel, and yet, as Nadia Fusini has pointed out, what readers ultimately witness is a miracle of transubstantiation whereby Plath transforms her writing into a living organism. To elaborate on this assertion, the article argues that, in Ariel, Plath no longer shields herself behind her masterful technique: instead, creator and creature must now become the same thing. This is the beginning of a process that will lead her not only to become a Poet, but to embody poetry.
Keywords: Sylvia Plath; Ariel; Transubstantiation; Rebirth; das Ding